Practice makes perfect complete Spanish all-in-one - Nissenberg, Gilda (Practice makes perfect, 2022)
This powerhouse program features all the knowledge and practice you need to master Spanish, drawn from five workbooks from the bestselling Practice Makes Perfect series. With Practice Makes Perfect : Complete Spanish All-in-One, you will build your Spanish vocabulary, straighten out your sentences, overcome fear of verb tenses, master the intricacies of grammar, and much more. This value-packed workbook covers all the facets of Spanish and offers thorough explanations that are reinforced by hundreds of hands-on practice exercises.